Urban and regional studies in the experience economy: What kind of turn? - Jeannerat, Hugues; Lorentzen, Anne (My University, 2013)
The paper introduces a special issue on ‘the experience turn in development and planning’. It is argued that the notion of the experience economy is able to challenge established theories of the culture economy in three ways. First, by placing consumption and consumers as point of departure for innovation and valuation. Secondly, by approaching place as valuable for consumption, and finally by turning the lens of planning towards places as destinations, which entails complex quality of place concerns. The papers of the issue contribute from three different but related perspectives. One perspective is to deconstruct economic value and innovation in regional studies and elaborate on the role of consumers and stages of consumption. Another is the actor perspective and the question of how localized networks of innovative actors evolve and engage in experiential staging. Finally the experience economy is seen as an integrated approach in policy and strategic planning on as well as across different scales. Future research should not only trace the evolution of experience offerings, stages and destinations and its possible dependence on specific economic phases and contexts. It should also develop further the potentials of the experience economy approach as a new perspective on economic phenomena as well as on territorial development.
Keywords: Economic geography; urban and regional development; urban planning; innovation; experience economy